Immunological Functions of the Omentum. Issue 7 (July 2017) - Meza-Perez, Selene; Randall, Troy D.
Abstract : The omentum is a visceral adipose tissue with unique immune functions. Although it is primarily an adipose tissue, the omentum also contains lymphoid aggregates, called milky spots (MSs), that contribute to peritoneal immunity by collecting antigens, particulates, and pathogens from the peritoneal cavity and, depending on the stimuli, promoting a variety of immune responses, including inflammation, tolerance, or even fibrosis. Reciprocal interactions between cells in the MS and adipocytes regulate their immune and metabolic functions. Importantly, the omentum collects metastasizing tumor cells and supports tumor growth by immunological and metabolic mechanisms. Here we summarize our current knowledge about the development, organization, and function of the omentum in peritoneal immunity. Trends: VAT-associated Tregs are a transcriptionally and functionally unique population of Tregs that regulate immune responses and metabolic processes in adipose tissues, including the omentum. ILC2 cells are found in adipose tissues like the omentum, where they regulate local immune responses and adipocyte metabolism. The omentum is a well characterized site of ovarian cancer metastasis, due to its ability to collect tumor cells from the peritoneal cavity and to support tumor cell metabolism and growth. Despite the immune functions of the omentum, it appears unable to promote adaptive immune response to tumors that implant in the milky spots.